2020
DOI: 10.1097/mou.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic alterations of testicular germ cell tumours

Abstract: Purpose of review Testicular germ cell tumours (TGCTs) exhibit, in contrast to other cancer types, a relatively low mutational burden. However, numerous epigenetic alterations have been shown to impact TGCT. In this review, we summarize the most relevant findings of the past 2 years. Recent findings Recent studies focused on the functions of microRNAs and the impact of aberrant DNA methylation. Moreover, several epigenetic drugs with antineoplastic effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A shift from gene body to promoter methylation is associated with decreased gene expression in resistant cells (combination of Group 1 and 3) and a shift from gene promoter to gene body CpG methylation is associated the inherent sensitivity of TGCTs [10][11][12][13]34]. TGCTs have distinct epigenetics, including distinct patterns of DNA methylation, and also have few somatic mutations suggesting that epigenetics may be a key driver of TGCT biology [35][36][37]. This has led to a popular recent proposal that DNA hypomethylation is a mechanism for TGCT cisplatin hypersensitivity and reciprocally DNA hypermethylation is a mechanism for cisplatin resistance [11,12,26].…”
Section: Discussionmentioning
confidence: 99%
“…A shift from gene body to promoter methylation is associated with decreased gene expression in resistant cells (combination of Group 1 and 3) and a shift from gene promoter to gene body CpG methylation is associated the inherent sensitivity of TGCTs [10][11][12][13]34]. TGCTs have distinct epigenetics, including distinct patterns of DNA methylation, and also have few somatic mutations suggesting that epigenetics may be a key driver of TGCT biology [35][36][37]. This has led to a popular recent proposal that DNA hypomethylation is a mechanism for TGCT cisplatin hypersensitivity and reciprocally DNA hypermethylation is a mechanism for cisplatin resistance [11,12,26].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the pathogenesis of testicular tumors is not clear. Epidemiological analysis has found that various factors increase the chance of TGCT, including congenital factors such as cryptorchidism or undescended testes, Klinefelter syndrome, testicular feminization syndrome, acquired factors such as injury, infection, nutritional factors, and excessive use of exogenous estrogen by the mother during pregnancy [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%